Association Between Serum Uric Acid Level and Psoriasis: A Case Control Study - Aruna Sayami; Aatmaram Gupta; Narayan Gautam (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Psoriasis is a common, chronic, inflammatory and proliferative condition of the skin, associated with various disorders including metabolic syndrome. High serum uric acid levels are also associated with metabolic syndrome. Hyperuricemia is associated with psoriasis and psoriatic arthritis.